Yahoo Answers is shutting down on May 4th, 2021 (Eastern Time) and beginning April 20th, 2021 (Eastern Time) the Yahoo Answers website will be in read-only mode. There will be no changes to other Yahoo properties or services, or your Yahoo account. You can find more information about the Yahoo Answers shutdown and how to download your data on this help page.
Trending News
Differentiation of a quotient of two function?
Question: y=Cosx/x^4
Answer : dy/dx=x^4(-sinx)-cosx(4x^3) / x^8
= -xsinx - 4cosx / x^5
Okay I have a question regarding the final part of the answer -xsinx - 4cosx / x^5 , how is this worked out. I got to the point of dy/dx=x^4(-sinx)-cosx(4x^3) / x^8 but after that I'm confused. Why does x^4(-sinx) become -xsinx on the last step, similarly -cosx(4x^3) to - 4cosx and x^8 to x^5. confused and I need some help. Thank you.
okay I think I just figured it out...after first step I did this : x^3(-xcosx-4cosx) / x^8, note: this is same as x^4(-sinx)-cosx(4x^3) / x^8 , so I subtracted x^3 by the denominator x^8 which gave me x^5...the x^3 from the top cancels out...Correct me if I'm wrong, please. thank you.
2 Answers
- Anonymous9 years agoFavorite Answer
y = cos(x) / x^4
Can be written as:
y = x^(-4) * cos(x)
Using the product rule:
dy/dx = d/dx (x^(-4)) * cos(x) + x^(-4) * d/dx (cos(x))
dy/dx = -4x^(-5) * cos(x) + x^(-4) * -sin(x)
dy/dx = -4cos(x) / (x^5) - sin(x) / (x^4)
Make them the same denominator by multiplying the second fraction by x/x:
dy/dx = (-4cos(x) - xsin(x)) / (x^5)
I hope this clears things up :)
- 9 years ago
Ok so when you have dy/dx=x^4(-sinx)-cosx(4x^3) / x^8, multiply each term in the equation by x^-3 (ie drop the power of each x by 3)
dy/dx=x^1(-sinx)-cosx(4x^0) / x^5
= -xsinx - 4cosx / x^5